Kajian Literatur: Hubungan Pengetahuan Keselamatan dan Kesehatan Kerja dengan Kecelakaan Kerja - Nisa Zakiati Umami (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
The role of occupational safety and health is crucial to support the productivity of worker performance. Good occupational safety and health knowledge can minimize workplace accidents. The study aimed to determine the relationship between the level of occupational safety and health knowledge and work accident. This research uses the literature study method. The libraries used are 3 articles from the official website, 2 books from Google Books, and 8 journals from Google Scholar with a range of publications for the last 10 years (2012-2022). This research was conducted by identifying previous studies related to the title, namely the relationship between knowledge of Occupational Safety and Health and work accidents. Researchers took several journals that stated a relationship between knowledge of occupational safety and health and work accidents. The conclusion is that there is a relationship between knowledge of occupational safety and health and work accidents. The advice is that it is necessary to do further research related to the factors that affect the ability of occupational safety and health about work accidents.